Células da resposta imune em mulheres portadoras de candidíase vulvovaginal - Queiroz Filho, José (2006)
Vulvovaginal candidiasis (VVC) is one of the most common infections in the clinical practice of a gynecologist. and control of this disease is carried out by various defense mechanisms, where the cellular immune response appears to be fundamental. In order to investigate the cellular immune response in women with and without CVV, Peripheral blood cells of vaginal mucosa were evaluated, the concentrations of total and specific IgE to Candida albicans, 60 women and 40 with VVC and 20 as a control group, aged 10 to 60 years years served in the gynecology service Hapvida health complex in Natal (RN) in the period January-March 2006. Peripheral blood samples were taken by venipuncture and cell count of each patient was performed by automation and manual counting in blood smears stained with Giemsa. Quantification of CD4 + and CD8 + lymphocytes was performed by flow cytometry Vaginal smears were prepared with shaved lateral vaginal wall, The slides were fixed immediately in absolute ethanol and then stained with hematoxylin-eosin, 10 were analyzed by microscopic fields blades eyepiece 10X and 40X objective. The serum IgE concentrations and total specific for Candida albicans, They were obtained by chemiluminescence and fluoroimmunoassay. In peripheral blood and vaginal shaved studied cell type cell neutrophils, lymphocytes, eosinophils and monocytes. Statistical analysis was performed using the Fisher exact test and nonparametric Kruskal-Wallis, Mann-Whitney and Spearman correlation test In the group of women with VVC cell analysis in peripheral blood eosinophil predominated, (average 302.60) and this significant finding with p = 0.037 in the control group. . The cell study the cells in vaginal scrapings showed significant differences in neutrophils neutrophils, (average 230.70) and lymphocytes (average 11.50) with significance of p = 0.0001. .With Respect to quantification of CD4 + T lymphocytes and CD8 + there was no statistical significance. IgE serum concentrations and specific overall did not show statistical significance and and both groups the results were similar in the different methodologies. By relating the total serum IgE concentrations (mean = 308.83), with eosinophils in the peripheral blood of women with VVC had a 0.25 considered low correlation index.